Legal Review Of The Role Of The Police In Combating Online Gambling Crime Based On Criminology Theory (Case Study In The Jurisdiction Of The Bengkulu City Police) - Ramadhan Syaipullah; Ferawati Royani; Widya Timur (Fakultas Hukum Dehasen, 2026)
Online gambling is a crime that continues to grow with advances in information technology. Although prohibited by Articles 303 and 303 bis of the Criminal Code and the Electronic Information and Transactions (ITE) Law, this practice remains widespread due to its anonymous, cross-border, and digital nature. This phenomenon also occurs within the jurisdiction of the Bengkulu City Police, marked by an increase in the number of online gambling cases handled. This study aims to analyze the role of the Bengkulu City Police in combating online gambling and assess the effectiveness of its legal regulations based on criminological theory. The method used is empirical juridical legal research through literature review and interviews. The results show that the Bengkulu City Police have implemented preventive, preemptive, and repressive efforts through outreach, cyber patrols, law enforcement, and collaboration with relevant agencies. However, implementation still faces obstacles such as limited resources, the technological sophistication of perpetrators, and low digital literacy among the public. Based on the theories of social control and differential association, online gambling is influenced by weak social oversight and the digital environment. This study concludes that the role of the police has been running, but not optimally, so that it is necessary to strengthen regulations, increase the capacity of officers, and synergy between related parties.